Evaluasi Terhadap Program Franchise Studi Kasus Alfamart di Indonesia - Rosiyani Oktavia; Giantoro Pamungkas; Ela Rosita; Robiyatul Aniyah; Haris Munandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The evaluation of the Alfamart franchise program in Indonesia aims to analyze the effectiveness and sustainability of this business model. This research involves interviews with franchise owners as well as quantitative data analysis regarding the growth in the number of outlets. The results obtained show that by 2024, Alfamart will succeed in reaching more than 23,670 outlets, with a franchise strategy that has proven effective in expanding the distribution network. However, there are challenges that need to be overcome, such as improving marketing communications and cultural adaptation in new markets, so that long-term success can be guaranteed.